Distinct projection targets define subpopulations of mouse brainstem vagal neurons that express the autism‐associated MET receptor tyrosine kinase. Issue 18 (11th October 2017) - Kamitakahara, Anna; Wu, Hsiao‐Huei; Levitt, Pat
Abstract: Detailed anatomical tracing and mapping of the viscerotopic organization of the vagal motor nuclei has provided insight into autonomic function in health and disease. To further define specific cellular identities, we paired information based on visceral connectivity with a cell‐type specific marker of a subpopulation of neurons in the dorsal motor nucleus of the vagus (DMV) and nucleus ambiguus (nAmb) that express the autism‐associated MET receptor tyrosine kinase. As gastrointestinal disturbances are common in children with autism spectrum disorder (ASD), we sought to define the relationship between MET‐expressing (MET+) neurons in the DMV and nAmb, and the gastrointestinal tract. Using wholemount tissue staining and clearing, or retrograde tracing in a MET EGFP transgenic mouse, we identify three novel subpopulations of EGFP+ vagal brainstem neurons: (a) EGFP+ neurons in the nAmb projecting to the esophagus or laryngeal muscles, (b) EGFP+ neurons in the medial DMV projecting to the stomach, and (b) EGFP+ neurons in the lateral DMV projecting to the cecum and/or proximal colon. Expression of the MET ligand, hepatocyte growth factor (HGF), by tissues innervated by vagal motor neurons during fetal development reveal potential sites of HGF‐MET interaction. Furthermore, similar cellular expression patterns of MET in the brainstem of both the mouse and nonhuman primate suggests that MET expression at these sites is evolutionarily conserved. Together, the data suggest that MET+ neurons in the brainstem vagal motor nuclei are anatomically positioned to regulate distinct portions of the gastrointestinal tract, with implications for the pathophysiology of gastrointestinal comorbidities of ASD.